Angels and devils: sadism and violence in children. Issue 3 (1st September 2016) - Music, Graham
Abstract : This paper looks at violence and sadism in child and adolescent patients. Psychoanalytic and developmental ideas are brought together to make sense of these children's presentations and the clinical challenges of therapeutic work with them. Differences are outlined between cold and hotter forms of aggression. The contribution of Glasser and his concept of the core complex is central to the paper, as is an understanding of addictive processes often seen in aggression, including sexual aggression.